Air and water oxidation of aluminum flake particles; Advanced Powder Technology; Vol. 307 - Antipina S. A. Svetlana Anatolievna; Zmanovskii S. V. Sergey Vladislavovich; Gromov A. A. Aleksandr Aleksandrovich; Teipel U. Ulrich (2017, 2017)
Title screen